Glacial lakes in the Horgos river basin and their outbreak risk assessment - A. P. Medeu; T. G. Tokmagambetov; A. L. Kokarev; P. A. Plekhanov; N. S. Plekhanova (Лëд и снег, 2015)
The river Khorgos (in Kazakhstan – Korgas) is a boundary river between Kazakhstan and China. Its basin is located in the central part of southern slope of Dzhungarskiy (Zhetysu) Alatau range. According to agreement between Kazakhstan and China at the boundary transition of Khorgos in the floodplain of the river Khorgos the large Center of Frontier Cooperation is erected. Estimation of safety of the mentioned object including connection with possible glacial lakes outbursts has the importance of political-economical value. Nowadays development of glacial lakes in the overhead part of Khorgos river basin has reached apogee. As a roof we can mention the maximum of total glacial lakes area (1,7 million m² in 41 lakes) and emptied kettles of former glacial lakes. Six lakes reached highly dangerous outburst stage: the volume of lakes reached some million m³, maximum depth up to 30–40 m. Focal ground filtration of the water from lakes takes place. Development of glacial lakes in Khorgos river basin will continue, and these lakes give and will give real danger for the Center of Frontier Cooperation in case of outburst of naturally dammed lake Kazankol with the similar mechanism of Issyk lake outburst, occurred in 1963 in ZailijskiyAlatau (Ile Alatau).